2012
DOI: 10.3390/nu4070695
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Exposure Alters Mouse Lung Inflammation in Response to Inhaled Dust

Abstract: Alcohol exposure is associated with increased lung infections and decreased mucociliary clearance. Occupational workers exposed to dusts from concentrated animal feeding operations (CAFOs) are at risk for developing chronic inflammatory lung diseases. Agricultural worker co-exposure to alcohol and organic dust has been established, although little research has been conducted on the combination effects of alcohol and organic dusts on the lung. Previously, we have shown in a mouse model that exposure to hog dust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…In our study, we observed pro-inflammatory cytokines that are responsible for neutrophil and lymphocyte recruitment increase with a 5% HDE exposure in the BEAS-2B cell line. We also observed a blunting effect in the airway cells that were exposed to HDE and EtOH, which would be in accordance with our in vivo model histological findings (McCaskill et al, 2012). A decrease in pro-inflammatory cytokines (TNFα, IL-6, IL-8) as seen in Figures 1, 5 and 6 corroborates the published observations of decreased lung lavage lymphocytes and mononuclear cell aggregates in alcohol-fed mice challenged with HDE.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, we observed pro-inflammatory cytokines that are responsible for neutrophil and lymphocyte recruitment increase with a 5% HDE exposure in the BEAS-2B cell line. We also observed a blunting effect in the airway cells that were exposed to HDE and EtOH, which would be in accordance with our in vivo model histological findings (McCaskill et al, 2012). A decrease in pro-inflammatory cytokines (TNFα, IL-6, IL-8) as seen in Figures 1, 5 and 6 corroborates the published observations of decreased lung lavage lymphocytes and mononuclear cell aggregates in alcohol-fed mice challenged with HDE.…”
Section: Discussionsupporting
confidence: 91%
“…In studies conducted with a mouse model, mice that consumed ad libitum EtOH for 6 wk and inhaled HDE for 3 wk had fewer neutrophils and lymphocytes present in bronchoalveolar lavage fluid (BALF) compared to mice that were only exposed to HDE (McCaskill et al, 2012). In our study, we observed pro-inflammatory cytokines that are responsible for neutrophil and lymphocyte recruitment increase with a 5% HDE exposure in the BEAS-2B cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision-cut lung (PCL) slices were made as previously described (14). Briefly, C57BL/6 mice were killed, and the lungs were inflated with low-melting-point agarose (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…All animals were given standard chow ad libitum; dietary intake was comparable in both groups. With these general approaches, the blood alcohol levels of animals following chronic ethanol consumption has been reported to be 0.08% (38,54).…”
Section: Reagentsmentioning
confidence: 99%